Arquitectura, corpo e cognição: uma reflexão sobre a experiência perceptiva no arquitectónico - Rute Morais Peixoto (2015)
This dissertation tackles the matter of the perceptual experience within the scope of architecture. Herein is proposed the introduction of the body and the senses as indissociable parts of a system in the architectural discussion and practice. Drawing mainly upon the books The Eyes of the Skin and The Thinking Hand by the architect Juhani Pallasmaa, as well as the writings of other multidisciplinary authors that approach the Phenomenology field in their works, some notes are taken regarding the importance of a multisensory and manual approach to the artistic endeavor. First, the complicity between body and mind is clarified; then, each of our cognitive faculties is presented, emphasizing the tendency to favor sight over the other senses throughout History. Thus, this work seeks to explain the way all senses work together towards our experience of the world. Furthermore, the influence of the human memory in the dynamics of perception is investigated, resorting to Edward Casey's essay Public Memory in Place and Time in order to distinguish its particularities. Moreover, the matter of verbal and body language as essential communicative abilities of the human condition is introduced, highlighting the hand that, given its tactile specialization, becomes the protagonist of the haptic activity in the context of the last chapters of this dissertation. Subsequently, the inferred information is applied to the field of architecture, in a more specific fashion. The impact of the current "visual supremacy" in the creative process is explored, in addition to the role the resulting sensorial unbalance plays in numbing our contact with the world. Focusing on concepts such as time, space, materiality, and image, work methods that promote manual and haptic engagement are suggested, instead of processes that are mediated by machines which, in a way, filter out part of the natural capacity to project the sensorial information we store in our bodies during the existential experience. The purpose of this work is to create awareness about the expressive value of positioning our physicality and perceptual sensitivity in the center of the architectural practice thus enabling the optimization of the creative process.